KEMBALINYA PUSAT HIBURAN KEBUDAYAAN DI THR LOKASARI, JAKARTA BARAT - Paramitha Mauina Hartanto; Sidhi Wiguna Teh (Jurusan Arsitektur dan Perencanaan, 2022)
The phenomenon of degradation does not only occur in humans, but can also occur in an area. Degradation both functionally and morally occurred in the Lokasari THR area, Taman Sari District, West Jakarta. The degradation that occurs is that the area that was once known as the center of cultural entertainment in Batavia is now inversely becoming an area that is rarely touched and contains nightlife so it is considered dangerous. The aim of the project is to deal with existing degradation by turning Lokasari back into a positive cultural entertainment area and providing a place for local people to gather. It is hoped that the project will also be useful as a city magnet, a place for recreation from daily activities, and again to experience the beautiful memories they once had in the Lokasari THR area. This research uses borrowed design methods to get space programs and typology design methods to get the shape of the mass composition. From the existing background, the Lok(Art-H)sari Cultural Center is now present and is intended to revive cultural elements in the Lokasari area. The project will be a place where people can also gather, interact, and have fun. The cultural center will bring back various programs that have become Lokasari's memories by including additions and adding a touch of modern adjustments to give an interesting impression. The memory of the culture that is very attached to the area is used as a